Decoloniality and the religious experience of “double belonging”: A look from the frontier subjectivity - Caldeira, Cleusa (2023)
This article does not only intend to talk about decoloniality, but above all, to present itself as a text situated in subalternity, that is, as a text produced by and for subalternity. It is about following the assumption of the political-epistemic project of decoloniality in bringing out the subaltern as thinker, creator, and activist capable of fomenting a different knowledge that is the bearer of the expression of a new world, a more plural world.  We will divide the text into two parts. In the first, we recover some basic concepts about what the political-epistemic project of decoloniality is. In this way, the study of religion will not run the risk of reducing decoloniality to one more theme among other themes to be studied academically. In the second part, we seek to remove from invisibility the religious experience of "double belonging" of Black Christians and the need to establish a South-South epistemological dialogue for the consolidation of a Black Christianity.